2010
DOI: 10.1007/s12192-009-0123-z
|View full text |Cite
|
Sign up to set email alerts
|

A SNP in the HSP90AA1 gene 5′ flanking region is associated with the adaptation to differential thermal conditions in the ovine species

Abstract: Molecular chaperones have long been understood to be preferentially transcribed in response to multiple perturbations of the cellular homeostasis. In this study, several polymorphisms in the gene encoding the inducible form of the cytoplasmic Hsp90 (HSP90AA1) were addressed in 24 sheep breeds reared in different climatic regions of Europe, Africa, and Asia. Significant differences in the genotype frequencies for a C/G single nucleotide polymorphism (SNP) located at position -660 in the HSP90AA1 5'flanking regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 33 publications
(35 reference statements)
1
34
1
1
Order By: Relevance
“…In this study, as breeds are located in a more restricted geographic area (different locations in Turkey), with less climatic differences, the results are not as evident as in the study developed by Marcos-Carcavilla et al (2010b). Differences observed between breeds demonstrated the existence of a northsouth division that might be due to historic causes, such as different ancestors from which north and south populations were originated.…”
Section: Resultscontrasting
confidence: 58%
See 1 more Smart Citation
“…In this study, as breeds are located in a more restricted geographic area (different locations in Turkey), with less climatic differences, the results are not as evident as in the study developed by Marcos-Carcavilla et al (2010b). Differences observed between breeds demonstrated the existence of a northsouth division that might be due to historic causes, such as different ancestors from which north and south populations were originated.…”
Section: Resultscontrasting
confidence: 58%
“…A 300 bp region of the 5 0 flanking region of the HSP90AA1 gene was amplified as previously described by Marcos-Carcavilla et al (2010b). The resulting PCR fragments were purified with a Macherey-Nagel Extract II purification kit (GmbH & Co., KG) and sequenced with specific primers, also reported by Marcos-Carcavilla et al (2010b).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, in a parallel study (Marcos-Carcavilla et al 2009) performed on ARR/ARR Manchega sheep breed, it has been observed that after several days of high temperatures, HSP90AA1 expression increased significantly (p< 0.05) in animals bearing the CC −660 AA −528 genotype. Conversely, no significant differences were detected in their CG −660 AG −528 counterparts.…”
Section: Discussionmentioning
confidence: 93%
“…Hsp90α is necessary for spermatogenesis and meiotic progression in mammalian testis (Grad et al 2010). The ovine HSP90AA1 gene has been studied thoroughly by our group since 2008 (Marcos-Carcavilla et al 2008, 2010aOner et al 2012;Salces-Ortiz et al 2013, 2015a. A recent functional analysis of the ovine HSP90AA1 gene (Salces-Ortiz et al 2015c) has demonstrated that two linked polymorphisms, a cytosine insertion (g.667_668insC; rs397514115) and a C to G transversion (g.660G>C; rs397514116), both located at the promoter region, are mainly responsible for the observed differences in the expression rate of the gene in response to heat stress events.…”
Section: Introductionmentioning
confidence: 99%